Targeting Recruitment of Disruptor of Telomeric Silencing 1-like (DOT1L): CHARACTERIZING THE INTERACTIONS BETWEEN DOT1L AND MIXED LINEAGE LEUKEMIA (MLL) FUSION PROTEINS - Shen, Chenxi (American Society for Biochemistry and Molecular Biology, 2013)
The MLL fusion proteins, AF9 and ENL, activate target genes in part via recruitment of the histone methyltransferase DOT1L (disruptor of telomeric silencing 1-like). Here we report biochemical, biophysical, and functional characterization of the interaction between DOT1L and MLL fusion proteins, AF9/ENL. The AF9/ENL-binding site in human DOT1L was mapped, and the interaction site was identified to a 10-amino acid region (DOT1L(865–874)). This region is highly conserved in DOT1L from a variety of species. Alanine scanning mutagenesis analysis shows that four conserved hydrophobic residues from the identified binding motif are essential for the interactions with AF9/ENL. Binding studies demonstrate that the entire intact C-terminal domain of AF9/ENL is required for optimal interaction with DOT1L. Functional studies show that the mapped AF9/ENL interacting site is essential for immortalization by MLL-AF9, indicating that DOT1L interaction with MLL-AF9 and its recruitment are required for transformation by MLL-AF9. These results strongly suggest that disruption of interaction between DOT1L and AF9/ENL is a promising therapeutic strategy with potentially fewer adverse effects than enzymatic inhibition of DOT1L for MLL fusion protein-associated leukemia.